Digital Disinformation and Electoral Law: Challenges and Solutions to Strengthen the Legitimacy of Elections (CIPEEX, 2025)
The research analyzes how disinformation spreads rapidly on social media during Brazilian elections,affecting voters’ trust and intensifying polarization. Algorithms that prioritize content confirming pre-existing beliefs create “information bubbles,” expanding the reach of fake news and undermining theintegrity of the electoral process. The study aims to understand how digital disinformation challengesthe legitimacy of the electoral process in Brazil and, based on this analysis, to suggestrecommendations that strengthen democracy. A qualitative approach was used, based on a systematicliterature review and an interpretive analysis of emblematic cases of false-news propagation. Thismethodology made it possible to identify dissemination mechanisms and the impacts of digital-manipulation strategies. The combination of automated accounts (bots) and human operators (trolls)creates the appearance of spontaneous engagement but, in reality, promotes the amplification ofdistorted narratives. Furthermore, the Brazilian electoral legal framework proves to be outdated in theface of technological innovations, revealing a lack of real-time auditing and transparency in thecirculation of information, especially within private communication channels. To restore thecredibility of electoral contests, the study proposes updating the regulation of digital platforms withcontinuous audits and graduated sanctions, implementing media literacy campaigns, and strengtheningcooperation among the Judiciary, electoral authorities, and civil society.
Keywords: digital disinformation; electoral law; fake news; social media; democracy.